Analisis Kewenangan Pemerintah Daerah Kota Bukittinggi dalam Penanggulangan Inflasi Cabai Berdasarkan Undang-Undang Nomor 23 Tahun 2014 tentang Kewenangan Pemerintahan Daerah dalam Perspektif Siyasah Maliyah - Meri Ruzalia; Ismail Ismail (Lembaga Yasin AlSys, 2026)
The phenomenon of chili inflation in Bukittinggi City has become a regional economic problem that directly affects people’s purchasing power and food price stability. In September 2025, the price of chili reached IDR 90,000 per kilogram, while in February 2026 it remained in the range of IDR 50,000–60,000 per kilogram. This condition indicates high price fluctuations influenced by limited supply, dependence on supporting regions, and inefficient distribution. This study aims to analyze the authority of the Bukittinggi City Regional Government in addressing chili inflation based on Law Number 23 of 2014 concerning Regional Government and to examine its implementation from the perspective of Siyasah Maliyah. This study used field research with a normative-empirical qualitative approach. Data were obtained through observation, interviews, and documentation with informants from relevant agencies and chili traders at Aur Kuning Market. The data were analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the Bukittinggi City Regional Government has legitimate authority in controlling chili inflation through policies on local chili cultivation, the mixing of local and outside-region chili supplies, shortening the distribution chain, strengthening farmer institutions, and developing food infrastructure. From the perspective of Siyasah Maliyah, these policies generally reflect the principles of al-‘adl, maslahah ‘ammah, and the maxim tasharruf al-imam ‘ala al-ra’iyyah manuthun bil maslahah. This study contributes to the development of studies on regional government law and Islamic economics, particularly in understanding the authority of regional governments in maintaining food stability. The implications of this study emphasize the importance of food inflation governance based on regional authority, distributive justice, public benefit, and the strengthening of local supply resilience.